PENGEMBANGAN TES DIAGNOSTIK TWO-TIER PADA MATERI GERAK MELINGKAR BERATURAN DI SMA - Yuliarni, Ulfa; Maria S, Haratua Tiur; Mahmuda, Diah (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractResearch and development (R&D) aims to develop two-tier diagnostic test that can be used to explore students’ misconceptions on the uniform circular motion in senior high school. The diagnostic test is developed based on the initial concept of the student by adapting the 7 steps of Borg & Gall development. Total of 40 students in XI MIPA 1 of SMA Negeri 2 Pontianak involved in the preliminary field test. Meanwhile, in the main field test was conducted in XI MIPA 2 and XI MIPA 3 of SMA Negeri 2 Pontianak, XI MIPA 3 and XI MIPA 4 of SMA Negeri 7 Pontianak as well as XI MIPA 2 and XI MIPA 3 of SMA Negeri 8 Pontianak with total sampel of 221 students. The result is 25 items meet good test quality with level of content validity is 0.81 and reliability is 0.814. In addition, the diagnostic test also has difficulty levels with moderate-to-easy categories (0.31-0.85) and readability rates is 5.25, so it meet the characteristics of good diagnostic tests. In other words, developed diagnostic tests can be used to explore the misconceptions of students on uniform circular motion.Keywords: Diagnostic test, two-tier, uniform circular motion